2011
DOI: 10.1002/adsc.201000349
|View full text |Cite
|
Sign up to set email alerts
|

2,6‐Diisopropoxyphenyl(dicyclohexyl)phosphine: A New Ligand for Palladium‐Catalyzed Amination Reactions of Aryl Chlorides with Potassium Hydroxide as the Base

Abstract: A new, readily available monophosphine tetrafluoroborate salt [L2·HBF 4 ] was developed for the palladium-catalyzed amination reaction of aryl chlorides in moderate to high yields with the cheap and easily available potassium hydroxide as the base. The reaction enjoys a wide scope, lower reaction temperatures, shorter reaction times, high yields, and low catalyst loading when compared to some of same amination reactions reported in the literature. Based on a kinetic study, 31 P NMR measurements, and DFT calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 86 publications
0
11
0
2
Order By: Relevance
“…For these comparative tests, the triarylphosphines tested were PPh 3 (11), (o-anisyl)diphenylphosphine (12), (2,6-dimethoxyphenyl)diphenylphosphine (13) and 2-diphenylphosphanyl-2Ј-methylbiphenyl (14; Figure 4). [35] As a result, both elementary steps, oxidative addition and reductive elimination/product decoordination, should be facilitated. [34] Under the above optimised conditions, the conversions increased in the order 11 Ͻ 12 Ͻ 13 Ͻ 2 (Table 7).…”
Section: Suzuki-miyaura Reactions Of Aryl Bromides ϫ Comparison With mentioning
confidence: 99%
“…For these comparative tests, the triarylphosphines tested were PPh 3 (11), (o-anisyl)diphenylphosphine (12), (2,6-dimethoxyphenyl)diphenylphosphine (13) and 2-diphenylphosphanyl-2Ј-methylbiphenyl (14; Figure 4). [35] As a result, both elementary steps, oxidative addition and reductive elimination/product decoordination, should be facilitated. [34] Under the above optimised conditions, the conversions increased in the order 11 Ͻ 12 Ͻ 13 Ͻ 2 (Table 7).…”
Section: Suzuki-miyaura Reactions Of Aryl Bromides ϫ Comparison With mentioning
confidence: 99%
“…From these data it is concluded that SPhos takes mono‐ligation with Pd and prevents the β‐H elimination while Gorlos‐Phos prefers bis‐ligation with Pd. Then the Gorlos‐Phos‐mono‐ligated palladium intermediate Int 2 would have the free coordination sphere required by β‐H elimination, thus, facilitating β‐H elimination during the coupling reaction to afford the β‐H elimination‐based coupling product allene 3a , as confirmed by SAESI‐MS‐MS experiment of Int 2 (eqn. 15).…”
Section: Resultsmentioning
confidence: 79%
“…After some screening, we observed the exclusive formation of ethylation product allene 2a when SPhos was used (Table , entry 4). Other mono‐phosphine ligands such as MePhos, XPhos, or Zheda‐Phos (Table , entries 5, 7, 11) also afforded a mixture of ethylation product 2a and β‐H elimination product 3a with a high selectivity while the reactions with BrettPhos or t ‐BuXPhos gave rather poor results (Table , entries 6 and 8). The loadings of SPhos and diethyl zinc could be reduced to 7.5 mol% and 2.0 equiv., respectively (Table , entry 13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because PPh 3 was ineffective both in 1,4-dioxane with K 3 PO 4 and in toluene with K 2 CO 3 ( Table 1, Entries 1 and 4), Gorlos-Phos·HBF 4 [15] ( Figure 1) was tested instead. Because PPh 3 was ineffective both in 1,4-dioxane with K 3 PO 4 and in toluene with K 2 CO 3 ( Table 1, Entries 1 and 4), Gorlos-Phos·HBF 4 [15] ( Figure 1) was tested instead.…”
Section: Resultsmentioning
confidence: 99%